EFEKTIVITAS MODEL TEAM GAMES TOURNAMENTTERHADAP HASIL BELAJAR MATERI SISTEM PEREDARAN DARAH KELAS VIII SMP - Asmanto, Asmanto; Syamswisna, Syamswisna; Putri Panjaitan, Ruqiah Ganda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the effectiveness of cooperative learning model Team Games Tournament (TGT) toward students learning outcomes on blood circulation system in class VIII SMP Koperasi Pontianak. The research was quasi experimental design. The research done in class VIII A and VIII B year 2010/2011 with 42 students VIII A and 40 students VIII B, class VIII A as experiment and VIII B as control. The research divided into two sessions. Instruments form was 20 item multiple choice. The result of the research shown the average post-test score of experiment class was 13,25 and control class was 11,74. Mann Whitney test result with significant ?=5% obtain Zscore< Ztable -3,56< 1,96. It can conclude that was a learning outcomes difference between students teach use cooperative learning model TGT and student teach use conventional learning model on blood circulation system in class VIII SMP Koperasi Pontianak. Keywords: Effectiveness, TGT Learning Model, Learning Outcomes, Blood Circulation System